(untitled) (Southern Journal for Contemporary History, 2019)
Journal for Contemporary History / Southern Journal for Contemporary History Recently I have assumed editorship of the Journal for Contemporary History, housed at the University of the Free State, and this announcement is intended to introduce the new editorial team and also to signal some major changes in the Journal’s editorial direction.